Through the Eyes of Trauma – Understanding Ocular Injuries and Orbital Fractures in Road Traffic Accidents - Mohan Abhirrami; R Parthibavijayan; Sridhar Baratan (TNOA Journal of Ophthalmic Science and Research)
Aim: To study the spectrum of ophthalmic manifestations and visual outcomes in patients with orbital wall fracture following road traffic accidents (RTAs). Methods: This prospective observational study was conducted over 2 years at a tertiary eye care centre in Puducherry. Based on computed tomography scans, 140 patients were grouped into no wall, single wall, two-wall, and three or more wall fractures. Ophthalmic evaluations were done on days 1, 3, 7, and 14 and at 1st and 3rd months. Ocular trauma score (OTS) was used to assess severity of injury and visual prognosis. Results: Among 140 patients, 122 (87.1%) were males and 18 (12.9%) females. Closed globe injuries predominated. Common adnexal observations included periorbital oedema with ecchymosis (47%) and subconjunctival haemorrhage (64.5%) in the anterior segment. Commotio retinae was the most frequent posterior segment finding (18.6%) and the leading cause of visual loss, followed by traumatic optic neuropathy (8.6%) and vitreous haemorrhage (6.4%). Lateral wall fractures were most common (71.4%) with mid-facial fractures often associated. The main causes of injury were falls from two-wheelers (33.6%) and collisions (25%). Good visual prognosis (OTS 5) was observed in 79.28% of patients, while poorer outcomes were associated with three-wall fractures. Most affected individuals had not used protective measures. Conclusion: Orbital wall fractures and ocular injuries following RTAs are a major cause of avoidable visual morbidity. Promoting road safety and increasing public awareness particularly regarding the consistent use of protective gear such as helmets and seatbelts is crucial in reducing the incidence and severity of traffic-related injuries.